Bakti Sosial Teledentistry untuk Mengoptimalkan Pelayanan Pasien di Era New Normal Dentistry - Haria Fitri; Suci Rahma Sari; Nila Kasuma; Rahmi Khairani; Dedi Sumantri; Fildzah Nurul Fajrin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
Dental and oral health is essential for every individual, especially for carrying out functions such as eating, speaking, aesthetics and feeling comfortable throughout the day. Dentists recommend checking the patient's oral health every six months. The Covid-19 pandemic limits the community's social conditions, including the need for patients to get dental and oral services from dentists. In addition, the professional activity of a dentist is one of the jobs most at risk of contracting Covid-19 from patients. A social service activity aims to introduce the Teledentistry method to patients, Co-ass students, Preceptors, and the general public. Teledentistry is the examination and consultation of dental and oral disorders and treatment of patients to the dentist without going through a face-to-face visit, but with the help of an online application. Through teledentistry activities, a dentist can take anamnesis to patients, in which clinical examinations were carried out through consultation with pictures and videos facilitated by interactive virtual media. The oral diagnosis was obtained as initial information in planning further treatment, and supportive care was carried out in the form of patient education and an encouragement to habituation of healthy living behaviour.